What differentiates the entrepreneurs from non-entrepreneurs on nature and nurture? - Kazmi, Syed Zaheer Abbas; Khan, Samiuddin; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2017)
Based on the importance and contribution of entrepreneurship in economic development, it is vital to know that what underlying factors may promote the spirit of entrepreneurship? The entrepreneurship literature suggests two kinds of broader influencers or predictors for entrepreneurs and non-entrepreneurs “nature” and “nurture”. In this study “nature” includes the psychological or personality related factors; self-confidence, locus of control, risk-taking propensity and trust levels. The “nurture” is explained by the effects from society in general and friends and family in particular. To answer the question “What differentiates the entrepreneurs from non-entrepreneurs on nature and nurture?” we collected data through questionnaire from 155 respondents. The 70 respondents were entrepreneurs and 85 were non-entrepreneurs. Step-wise discriminant analysis was used to determine the discriminating factors for entrepreneurs from non-entrepreneurs. Results indicate that societal impacts, risk taking propensity and trust levels were significantly discriminating the two groups; entrepreneurs and non-entrepreneurs. The study has important implications for policy makers, academicians, researchers and potential entrepreneurs.JEL Code: L26, M13